The impact of e-wallet on informal farm entrepreneurship development in rural Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
Transforming agriculture from a largely subsistence enterprise to a profitable commercial venture is both a prerequisite and a driving force for accelerated development and sustainable growth in su b - Saharan Africa. The objective of this investigation is to assess the impact of the Federal Government of Nigeria (FGN) e - wallet programme on informal farm entrepreneurship development in rural Nigeria. Informal sector farmers are those that are not legal ly registered at the national level though could be connected to a registered association. The research is motivated by the absence of literature focusing on the problem statement or objective of study. One thousand, one hundred and fifty - two rural farmer s were sampled across the six geo - political zones of Nigeria. Results from the use of a bivariate probit model indicate that the mobile phone - based technology via the e - wallet programme is a critical factor that has enhanced farm entrepreneurship in rural Nigeria. However, results also show that the impact of mobile phones (as a channel to accessing and using modern agricultural inputs) is contingent on how mobile networks are able to link farmers who live in rural areas and work mainly in farming. The resu lts suggest that increasing mobile phone services in rural Nigeria enhances farmers' knowledge, information and adoption of improved farm inputs and by extension, spurs rural informal sector economic activities in sub - Saharan Africa. Implications for prac tice, policy and research are discussed.
Keywords: Q10; Q14; L96; O40; O55; 330; Informal sector's adoption; electronic wallet technologies; rural farmers' entrepreneurship; Nigeria; developing countries